Fizika okusov in nadgradnja detektorja LHCb - Dagarin, Miha (Matrika, 2019)
LHCb is one of the four detectors placed on the Large Hadron Collider (LHC). This article deals with the experiments carried out on LHCb and the functioning of the detector itself. In order to be able to conduct a new generation of experiments and to increase sample data the accelerator is to be upgraded, which will require an update of the measuring systems as well. The article presents the components of the LHCb spectrometer, focusing on its upgrades.
Keywords: detektorji delcev; fizika okusov; fizika osnovnih delcev; flavour physics; Large Hadron Collider; particle detectors; physics of elementary particles; Veliki hadronski trkalnik